Epistemic Exploitation - Berenstain, Nora (Ergo, an Open Access Journal of Philosophy, 2016)
Epistemic exploitation occurs when privileged persons compel marginalized persons to educate them about the nature of their oppression. I argue that epistemic exploitation is marked by unrecognized, uncompensated, emotionally taxing, coerced epistemic labor. The coercive and exploitative aspects of the phenomenon are exemplified by the unpaid nature of the educational labor and its associated opportunity costs, the double bind that marginalized persons must navigate when faced with the demand to educate, and the need for additional labor created by the default skepticism of the privileged. I explore the connections between epistemic exploitation and the two varieties of epistemic injustice that Fricker (2007) identifies, testimonial and hermeneutical injustice. I situate epistemic exploitation within Dotson’s (2012; 2014) framework of epistemic oppression, and I address the role that epistemic exploitation plays in maintaining active ignorance and upholding dominant epistemic frameworks.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; discours dominant; exploitation épistémique; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; inégalités; oppression épistémique; philosophie; privilèges; sciences humaines; systèmes d'oppressions; thématiques; travail; violences; éthique

BLOOD UNDER THE BRIDGE: REFLECTIONS ON “THINKING SEX” - Rubin, Gayle (GLQ: A Journal of Lesbian and Gay Studies, 2011)
This article reflects on the intellectual and political circumstances of the publication of Gayle Rubin's 1984 essay “Thinking Sex: Notes for a Radical Theory of the Politics of Sexuality.” In particular, the article considers the context of the feminist “sex wars” of the late 1970s and early 1980s, offering a detailed account of several of the period's key events, publications, and debates. The article also reflects on the relation between this moment in the history of feminism and the history of GLBT and queer scholarship over the past several decades.
Keywords: 1900-1999; 1960-1969; 1970-1979; LGBTQIA2+; amériques; approches et analyses; cours; discipline; discours dominant; féminisme pro-sexe; histoire et politique; militance; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sex wars; soc2014; systèmes d'oppressions; thématiques; travail; violences; états-unis; études de genres